EFFICACY OF COGNITIVE BEHAVIOURAL THERAPY ON STRESS, ANXIETY, AND DEPRESSION OF INFERTILE COUPLES : SYSTEMATIC REVIEW - Laurenso Lomi, Eldwin (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
This high rate of occurrence is connected to the underlying cause of infertility, the amount of time that a person has struggled with it, and the number of times that different treatment options have been attempted. There is a wide range of psychological impacts that can be caused by infertility, ranging from feelings of inadequacy and stress to adverse effects on interpersonal relationships, substantial sadness, and anxiety. Cognitive behavioral therapy, also known as CBT, is a type of psychological treatment that has been shown to be effective for a wide range of problems, including severe mental illness, marital problems, eating disorders, and anxiety disorders, as well as problems related to alcohol and drug use and problems related to substance abuse. CBT is also known by its acronym, CBT. There have been a great number of studies conducted on CBT, all of which testify to its capability to dramatically improve both functioning and quality of life. CBT therapy, in which patients are taught new thinking and behavior approaches to replace negative views about self, world, and future, is effective in detecting stressful circumstances and utilizing coping strategies. CBT counseling replaces negative thoughts of patients about self, world, and future. According to research, cognitive behavioral therapy (CBT) is reliably effective in reducing symptoms of stress and anxiety, but it has mixed results in treating depression.